US withdrawal from Afghanistan: new ‘old’ perspectives from Central Asia - Baizakova, Zh.I. (KSU Publ., 2020)
Paper covers the Deal signed on 29 February 2020 in Doha between the United States and Taliban on stopping the violence and major terms and conditions the deal entails. Central Asian and Russian perspectives are taken into account as well as detailed views from both Taliban and Washington. Immediately after the deal a new wave of violence broke out in Afghanistan between Taliban and official Afghan national forces and the army. Paper attempts to answer how exactly the deal might benefit the countries of Central Asia and contribute to the overall regional security. One of the goals is to identify the real meaning of the Deal between US and Taliban for Central Asian countries. Among the tasks of the papers are following: make an attempt to find out whether Taliban truly intends to fulfill its end of the bargain; to comprehend the extent of the relationship between Taliban and other terrorist organisations operating inside the country; to reveal turbulent relations between official Afghan government and Washington and how these impact upon the Deal. The results of this article are about the uncertain future of Central Asia as a region facing post-signing the Deal. Despite ongoing violence and terrorist attacks in the country, Taliban’s key objective is to capture the power back; whilst Islamic State plans to extend its influence across entire neighbourhood, including CA.
АҚШ-тың Ауғанстаннан шығуы: Орталық Азия елдері үшін жаңа «ескі» перспективалар
Выход США из Афганистана: новые «старые» перспективы для стран Центральной Азии
Keywords: Afghanistan; Taliban; Kazakhstan; Uzbekistan; Islamic State; United States; Ghani; peace settlement